Q & A on housing and land use for subdivision & condominium buyers and real estate practitioners - Claridades, Alvin T. (Quezon City, Philippines : Central Book Supply, 2016)
This work worth commending and recommending if only for its attempt to "laymanize" and simply the provisions of the various laws and regulations pertaining to housing and land use to the end that they are easily understood by its end-users.
Introduction -- Legal Mandate -- Historical Background -- Creation of the HUDCC -- Key Function of the HLURB -- HLURB's jurisdiction to regulate the real estate trade and business. -- Registration of projects -- Devolved functions -- 1. Questions & Answers (Q&A) on HLURB'S Technical Assistance to local government units (LGUS) for the Preparation and updating of their Comprehensive Land Use Plans (CLUP) -- 2. Q & A on the minimum design standards and requirements for Economic and socialized housing projects -- 3. Q & A on the regulation of subdivision and condominium development projects -- Q & A Homeowners Association (HOA)
Keywords: HOUSING -- PHILIPPINES